Penerapan Metode Iteratif dan Analisis Pieces dalam Pengembangan Sistem Kepegawaian PT XYZ - Hasan, Adhitya; Farisi, Ahmad; Dafid (Journal of Informatics and Advanced Computing (JIAC), 2024)
Efficient and effective employee data management is key to assessing individual performance within a company. This study identifies that the manual methods currently used by PT XYZ are time-consuming and inefficient, potentially leading to damage, loss, or lack of information. Therefore, this study aims to develop a web-based personnel information system using an iterative method and data collection through interviews. The system is built using the React JS framework and MySQL for data storage. Available features include the management of attendance data, leave, transfers, promotions, assignments, rewards, and penalties. The final results of the study show that this system functions well and can enhance the company's performance through more efficient data processing.